Respuesta :
You can't do that, because what you do to one side you have to do to the other, and so, you have to divide the entire left side term by x, so you'd get:
s/x + s = 60/x not s+s=60/x
s/x + s = 60/x not s+s=60/x
well
s+sx=60
if you divided both sides by x (same as multiplying by 1/x) you would do
(1/x)(s+sx)=(1/x)60
s/x+sx/x=60/x
s/x=s=60
the division carries over to both terms
undistribute s
s(1+x)=60
divide both sides by 1+x
s=[tex] \frac{60}{1+x} [/tex]
s+sx=60
if you divided both sides by x (same as multiplying by 1/x) you would do
(1/x)(s+sx)=(1/x)60
s/x+sx/x=60/x
s/x=s=60
the division carries over to both terms
undistribute s
s(1+x)=60
divide both sides by 1+x
s=[tex] \frac{60}{1+x} [/tex]